2011
DOI: 10.1002/anie.201005755
|View full text |Cite
|
Sign up to set email alerts
|

Nitridosilicates and Oxonitridosilicates: From Ceramic Materials to Structural and Functional Diversity

Abstract: Silicates are one of the most important classes of compounds on this planet, and more than 1000 silicates have been identified in the mineral kingdom. Additionally, several hundreds of artificial silicates have been synthesized. The substitution of oxygen by nitrogen leads to the structurally diverse and manifold class of nitridosilicates. Silicon nitride, one of the most important non-oxidic ceramic materials, is the binary parent compound of nitridosilicates, and it symbolizes the inherent material propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
332
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(358 citation statements)
references
References 211 publications
23
332
0
3
Order By: Relevance
“…While the M-N bond lengths increase with increasing degree of condensation, the Si-N bond lengths tend to decrease with increasing degree of condensation, as has previously been observed by Schnick et al 12,84 This can also be observed from the data shown in Fig. 5a: the average Si-N distance is relatively large in for example Ca 4 SiN 4 (1.791 Å) with very low degree of condensation, while relatively small in SrSi 7 N 10 (1.731 Å) with a very high degree of condensation.…”
Section: Bond Lengthssupporting
confidence: 65%
“…While the M-N bond lengths increase with increasing degree of condensation, the Si-N bond lengths tend to decrease with increasing degree of condensation, as has previously been observed by Schnick et al 12,84 This can also be observed from the data shown in Fig. 5a: the average Si-N distance is relatively large in for example Ca 4 SiN 4 (1.791 Å) with very low degree of condensation, while relatively small in SrSi 7 N 10 (1.731 Å) with a very high degree of condensation.…”
Section: Bond Lengthssupporting
confidence: 65%
“…[1,7,9,10] Nitride-based materials are more covalent than oxides, which improves thermal stability, and their greater crystal field splitting increases the red emission leading to warmer white light. [1,2,11,12] The chemistry of doped nitride phosphors is often complex…”
Section: Main Textmentioning
confidence: 99%
“…Although YAG and other garnet-type host lattices continue to be considered very promising materials, it should be noted that a variety of other classes of phosphors have been developed and are now attracting increased attention. Examples of such are silicates [189], nitrides [190][191][192], and oxy-nitrides [193,194], to name a few.…”
Section: Discussionmentioning
confidence: 99%